THE QUADRATIC ASSIGNMENT PROBLEM : SOME NEW RESULT AND GENERALIZATION - Faiz Ahyaningish et al. (Proceedings of ICMSA, 2005)
The Quadratic assignment problem is a combinatorial problem ofdeciding the placement of facilities in specified locations in such a wayas to minimize an function expressed in terms of distances betweenlocations and flows between facilities. The approach presented in thispaper is to treat is as a large quadratic programming problem withinteger resfictions on the variables. The integer requirements areinitially relaxed, and the nearest feasible solutions in then sought.schemes for accomplishing this are described, and their applicability tomore general problems is discussed.